Sketchnoting Based PJBL for Teaching to Junior High School EFL Students in Writing Structure - Resty Wahyuni; Khairun Niswa (Institut Agama Islam Negeri Palopo, 2024)
This research aimed to determine the significant increase of using Sketchnoting Based PJBL on Students’ writing skills Achievement in Narrative Text, especially in writing for narrative text. This research was conducted during the academic year 2023/2024 at SMP NEGERI 43 MEDAN. This quantitative research was conducted using an experimental research design. The subjects of the study were 60 eight-grades students from SMP NEGERI 43 MEDAN who were selected using a total sampling method and then divided into two groups. Class VIII-A 1 consists of 30 students as the Experimental Group and is taught using the Sketchnoting based PJBL Method, while Class VIII-B consists of 30 students as the Control Group and is taught using the Teacher Centered Learning Method. The data were acquired using a pre-test and a post-test, and then analyzed using the t-test formula in the SPSS version 22 program. The outcome indicated that the significance level was 0.001<0.05, and the difference between the post-test mean scores of the control and experimental groups was 75.33 and 88.07. According to the results of the analysis, the Ha (alternative hypothesis)was accepted, while the null hypothesis was rejected. The findings of this study indicate that the Sketchnoting based PJBL Method is more effective than the Teacher Centered Learning in writing skills achievement narrative text at SMP NEGERI 43 MEDAN, where the Sketchnoting based PJBLwas implemented.